2004
DOI: 10.1055/s-2004-818924
|View full text |Cite
|
Sign up to set email alerts
|

Antitubercular and Antiplasmodial Constituents ofAbrus precatorius

Abstract: A known isoflavanquinone, abruquinone B ( 1), and a new derivative, abruquinone G ( 2), were isolated from the aerial parts of Abrus precatorius. Chemical structures of these compounds were elucidated by spectral analyses. While 1 exhibited antitubercular, antiplasmodial and cytotoxic activities, compound 2 showed mild antiviral and cytotoxic activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The use of Trema orientalis for treatment of viral infections has been reported elsewhere [24], while the anti-inflammatory activity of Cleome gynandra is supported by anti-inflammatory activity of a methanol extract of the leaves against adjuvant-induced arthritis in rats [25]. Other proven claims are the hepatoprotective effect of Cajanus cajan ethanol extract in rats [40] and the antimalarial activity of Abrus precatorius [39] and Clerodendrum myricoides [52,53]. Orthosiphon suffrutescens does not yet has proof of the concept laboratory results, but it is used in Rwanda for the treatment of malaria [45].…”
Section: Resultsmentioning
confidence: 99%
“…The use of Trema orientalis for treatment of viral infections has been reported elsewhere [24], while the anti-inflammatory activity of Cleome gynandra is supported by anti-inflammatory activity of a methanol extract of the leaves against adjuvant-induced arthritis in rats [25]. Other proven claims are the hepatoprotective effect of Cajanus cajan ethanol extract in rats [40] and the antimalarial activity of Abrus precatorius [39] and Clerodendrum myricoides [52,53]. Orthosiphon suffrutescens does not yet has proof of the concept laboratory results, but it is used in Rwanda for the treatment of malaria [45].…”
Section: Resultsmentioning
confidence: 99%
“…The investigations of Muhammad and Amusa have reported the use of the stem bark of Abrus precatorius (Leguminosae-Caesalpinioideae) in the treatment of malaria [98]. Limmatvapirat et al isolated abruquinone B ( 86 ), which showed anti-plasmodial activity, with IC 50  = 1.5 μg mL −1 against the K1 strain of P. falciparum , from the stem bark of this plant [99]. Ajaiyeoba et al [100] also reported the use of the leaves and stem bark of Cassia siamea in the treatment of malaria.…”
Section: Fabaceae Ganodermataceae Lamiaceae and Loranthaceaementioning
confidence: 99%
“…An active component from the plant extract has been isolated and characterized as the isoflavanoid quinone, abruquinone which was shown (Limmatvapirat et al, 2004) to have an MIC of 12.5μg/mL against the M. tb. strain H 37 Rv.…”
Section: 0 Results and Discussionmentioning
confidence: 99%